2013
DOI: 10.1063/1.4824108
|View full text |Cite
|
Sign up to set email alerts
|

Inertial coalescence of droplets on a partially wetting substrate

Abstract: We consider the growth rate of the height of the connecting bridge in rapid surface-tension-driven coalescence of two identical droplets attached on a partially wetting substrate. For a wide range of contact angle values, the height of the bridge grows with time following a power law with a universal exponent of 2/3, up to a threshold time, beyond which a 1/2 exponent results, that is known for coalescence of freely-suspended droplets. In a narrow range of contact angle values close to 90°, this threshold time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…At this stage, h increases at a faster rate for larger actuation potential. Earlier studies have shown that in the inertial regime the growth of liquid bridge (perpendicular to the solid surface) is proportional to τ 1/2 for a contact angle of 90°. Thus, to identify more specific characteristics, the early growth of bridge height is plotted in log–log scale to compare with τ 1/2 proposition at the inset of Figure 5.…”
Section: Influence Of Electric Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…At this stage, h increases at a faster rate for larger actuation potential. Earlier studies have shown that in the inertial regime the growth of liquid bridge (perpendicular to the solid surface) is proportional to τ 1/2 for a contact angle of 90°. Thus, to identify more specific characteristics, the early growth of bridge height is plotted in log–log scale to compare with τ 1/2 proposition at the inset of Figure 5.…”
Section: Influence Of Electric Potentialmentioning
confidence: 99%
“…Earlier studies have shown that in the inertial regime the growth of liquid bridge (perpendicular to the solid surface) is proportional to τ 1/2 for a contact angle of 90°. Thus, to identify more specific characteristics, the early growth of bridge height is plotted in log–log scale to compare with τ 1/2 proposition at the inset of Figure 5. A good fit between numerical observations and hR0τ12 proves that, up to a certain time period, coalescence happens independently of the electric field influence.…”
Section: Influence Of Electric Potentialmentioning
confidence: 99%
“…The coalescence and interaction of sessile droplets has been the subject of intensive study in scientific literature [1][2][3][4][5][6][7][8][9], not least motivated by its relevance for industrial processes such as ink-jet printing or surface processing. These studies have revealed intriguing and frequently counterintuitive physics behind this ubiquitous process.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] In addition to the dynamics of liquid bridge, there is now the added feature of the motion of a three-phase contact line. [16][17][18][19] In addition to the dynamics of liquid bridge, there is now the added feature of the motion of a three-phase contact line.…”
Section: Introductionmentioning
confidence: 99%
“…Except for the study of free-droplet coalescence, the coalescence of two droplets on a solid surface is also received much attention. [16][17][18][19] In addition to the dynamics of liquid bridge, there is now the added feature of the motion of a three-phase contact line. A number of studies have shown that the initial conditions, 16 presence of capillary waves, 20 and contact line dissipation 21,22 that influence the dynamics of coalescence.…”
Section: Introductionmentioning
confidence: 99%